Entrepreneurship in Post-Communist Countries New Drivers Towards a Market Economy (Springer International Publishing, 2018)
This volume analyzes the barriers to, as well as new drivers for, entrepreneurial development in post-communist countries. The contributors present various country studies, mainly in the Balkans region, and investigate entrepreneurial behavior and best practices, financial instruments, factors for the success of small and medium-sized companies, and related policy implications. The book will appeal to scholars, policymakers and professionals interested in entrepreneurial obstacles and challenges in the countries of the Balkans region.